Strategi Pengelolaan Pariwisata Heritage Di Kota Sawahlunto Untuk Mendukung Pariwisata Berkelanjutan - Azizah, Nurul; Sukmawati, Puja; Khairunnisa, Ayang (Institut Seni Indonesia Padangpanjang, 2024)
The city of Sawahlunto, designated as a UNESCO World Heritage Site, has great potential as an international heritage tourism destination. However, challenges such as cultural preservation, local community empowerment, and infrastructure development are still major obstacles. This research aims to formulate a sustainable heritage tourism management strategy through a qualitative approach based on literature review. The results showed that the success of heritage tourism management in Sawahlunto depends on the preservation of cultural assets, participation of local communities, strengthening branding, and utilization of digital technology for promotion. Synergy among stakeholders, such as the government, community, and private sector, is crucial in supporting the implementation of this strategy. With a holistic approach, Sawahlunto has not only maintained its status as a world heritage site, but also become a model of sustainable heritage tourism destination in Indonesia.